A model for publishers to introduce globally fair and transparent pricing - Wise, Alicia; Jago, Dave; Mentink, Herman; Estelle, Lorraine (Insights the UKSG journal, 2025)
The transition of many academic journals from the subscription model to open access shifts payment for publishing services from readers to producers of knowledge. Although this transition makes publications openly accessible to readers globally, many authors and institutions worldwide face financial barriers to publishing in the journals they choose at affordable prices. In response, cOAlition S (an international consortium of funding organizations advocating for open access) commissioned Information Power to develop a globally equitable and sustainable pricing model for academic publishing. We recognize that many stakeholders prefer a scholarly publication ecosystem without charges of any kind, and particularly author-facing charges, for open access publishing. While charges remain part of the scholarly communication landscape, then we feel strongly that open and transparent data should be used to calculate more equitable prices that reflect local purchasing power. This article presents the model that has been developed, the guiding principles and tools developed to support implementation, along with background explanations of the key challenges to developing a framework that ensures authors contribute in line with their means. It also discusses stakeholder feedback and explores potential applications of the framework in achieving a fairer and more inclusive scholarly publishing landscape.